Dicalcium phosphate and Vitamin A for calves on winter bluestem pasture (Project 253-2) - Theurer, L.J.; Smith, E.F.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The 40 heifer calves,10 per lot, used in this experiment were good-to-choice Herefords from near Fort Davis, Texas, assigned on a random weight basis to their treatments. They were pastured together in a 190-acre bluestem pasture, penned three times weekly, divided into treatment groups, and fed experimental rations shown in Table 41. Dicalcium phosphate (0.1 pound per heifer daily) and Vitamin A (10,000 I.U. daily), when fed, was mixed with soybean meal.
Keywords: Beef; Dicalcium phosphate; Vitamin A; Bluestem pasture